2013
DOI: 10.1186/1477-7525-11-81
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of four different approaches to measuring health utility in depressed patients

Abstract: BackgroundA variety of instruments are used to measure health related quality of life. Few data exist on the performance and agreement of different instruments in a depressed population. The aim of this study was to investigate agreement between, and suitability of, the EQ-5D-3L, EQ-5D Visual Analogue Scale (EQ-5D VAS), SF-6D and SF-12 new algorithm for measuring health utility in depressed patients.MethodsThe intraclass correlation coefficient (ICC) and Bland and Altman approaches were used to assess agreemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 32 publications
1
26
0
Order By: Relevance
“…The acceptability of the different study PROMs was measured using completion rates at baseline and each of the two follow up time points (4 and 12 months post randomisation) [29, 30]. …”
Section: Methodsmentioning
confidence: 99%
“…The acceptability of the different study PROMs was measured using completion rates at baseline and each of the two follow up time points (4 and 12 months post randomisation) [29, 30]. …”
Section: Methodsmentioning
confidence: 99%
“…Wright et al (2014) 25 provided evidence that the programme is supporting research of clinical relevance. Turner et al (2013) 26 found that 95.7% of all HTA studies either have published, or will publish, a monograph in the HTA journal, and that that percentage increases to 98% for studies commissioned after 2002. Chinnery et al (2013) 27 showed that these publications were available promptly.…”
Section: Adding Value In Researchmentioning
confidence: 99%
“…753 They also worked out effective ways of conducting large-scale trials in primary care (interviewee).…”
Section: Stage 1: Inputs To Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Turner et al 6 reported that an instrument measuring health status should be responsive to changes. Consequently, responsiveness, which reflects the ability of a questionnaire to detect changes over time, is an important psychometric quality and an essential criterion for instrument selection when measuring stroke patient function.…”
Section: Introductionmentioning
confidence: 99%